CREDIBILITY COMMITMENT AND PEACE BUILDING IN THE NIGER DELTA REGION OF NIGERIA - CHINEDU EKPERECHUKWU ETI; SUNDAY DIDAM AUDU; GOODNEWS OSAH (International Studies Journal)
The occurrence of conflict is predicated on several factors. While some are caused by the neglect of early warning mechanisms, others are as a result of subversive reactions to disproportionate distribution of resources and power; and or failed interventions to the conflict. The conflict in the Niger Delta region of Nigeria has been primarily driven by grievances related to resource exploitation, environmental degradation, and socio-economic marginalization. Despite various intervention efforts aimed at addressing these issues and fostering peace, the region continues to experience periodic resurgences of violence. This study examines the critical factor of credibility commitment in the context of peacebuilding initiatives of the federal government of Nigeria and its influence on the resurgence of the conflict in the Niger Delta region. The method of data gathering is drawn from literature and biographic narratives of the actors and victims of the conflict. The study notes that credibility, whether perceived or actual, plays a vital role in the success of peacebuilding efforts in conflict societies. When stakeholders, including government authorities, international organizations, and local communities, perceive intervention programs as lacking credibility or sincerity, trust is eroded, and the likelihood of conflict resurgence increases. Furthermore, a lack of commitment to addressing underlying grievances and root causes of conflict, and implementing sustainable solutions, undermines the effectiveness of peacebuilding initiatives.